Demands or Resources? The Relationship Between HR Practices, Employee Engagement, and Emotional Exhaustion Within a Hybrid Model of Employment Relations. Issue 5 (9th March 2015) - Conway, Edel; Fu, Na; Monks, Kathy; Alfes, Kerstin; Bailey, Catherine
Abstract : This article explores the ways in which employees may experience and respond to tensions inherent in the mix of potentially conflicting human resource (HR) practices that compose hybrid models of employment relations. By drawing on the job demands–resources (JD‐R) literature and viewing HR practices as "demands" and "resources, " we explore the impact of performance management and employee voice practices on employee well‐being, as exemplified by engagement and emotional exhaustion, in a large public‐sector organization in Ireland. Our findings suggest that employee voice mechanisms may act as a resource in both enhancing engagement and in counterbalancing the demands presented by a performance management system, thus reducing the deleterious effects of emotional exhaustion. Our study extends understanding of hybrid models of human resource management (HRM) and of the ways in which employees manage the contradictory signals that such models may send in terms of performance expectations. © 2015 Wiley Periodicals, Inc.